Sources of Knowledge in Preferences and Identification of Fauna in Children of Rural and Urban Contexts - Nidia Yaneth Torres-Merchán; Luis Alfonso Salcedo-Plazas; Ángela Becerra-Niño; Wilson Valderrama (Revista Electrónica Educare)
This article analyzes the influence of mass media on primary school students when studying animal species. Images on taxonomic groups of wildlife transmit perceptions. Therefore, these transmitted perceptions are examined in 249 children from rural and urban elementary school aged 7 to 13 years old. This analysis used two PowerPoint presentations with images of endemic and non-endemic species. It is found that in urban and rural contexts, television and Internet are the means for further identification of the species presented. Concerning the perceptions, students have a preference for mammals and birds species. These data allow inferring the influence media can have on the knowledge of biodiversity and the promotion of care towards nature.